Antibacterial effect of root canal preparation and calcium hydroxide paste (Calen) intracanal dressing in primary teeth with apical periodontitis Efeito antibacteriano do preparo biomecânico e do curativo de demora com pasta à base de hidróxido de cálcio (Calen) em dentes decíduos com lesão periapical - Gisele Faria; Paulo Nelson-Filho; Aldevina Campos de Freitas; Sada Assed; Izabel Yoko Ito (University of São Paulo, 2005)
The aim of this study was to evaluate the antibacterial action of root canal mechanical preparation using 2.5% sodium hypochlorite as the irrigating solution and a calcium hydroxide paste as the antibacterial intracanal dressing in human primary teeth root canals with pulp necrosis and apical periodontitis by means of microbial culture. A total of 26 root canals of human primary teeth with pulp necrosis and apical periodontitis were used. Samples were collected before, 72h after biomechanical treatment and 72h after removal of the intracanal dressing. Comparison by Wilcoxon test showed that root canal mechanical preparation effectively eliminated all microorganisms in 20% of the root canals, and the intracanal dressing in 62.5%; however, the cumulative action of biomechanical treatment and intracanal dressing eliminated the microorganisms of 70% of the root canals (p<0.001). Isolated root canal mechanical preparation presented poorer microbiological results that those obtained with root canal mechanical preparation and the use of an intracanal dressing indicating the necessity of topical application of an intracanal medication between sessions in primary teeth with pulp necrosis and apical periodontitis. O objetivo do presente estudo foi avaliar, por meio de cultura bacteriológica, a ação antibacteriana do preparo biomecânico utilizando como solução irrigadora o hipoclorito de sódio a 2,5% e da pasta Calen utilizada como curativo de demora em canais radiculares de dentes decíduos de humanos com necrose pulpar e lesão periapical. Foram selecionados 26 dentes decíduos de humanos portadores de necrose pulpar e lesão periapical. As colheitas microbiológicas foram efetuadas antes e 72 horas após o preparo biomecânico e 72 horas após a remoção do curativo de demora. A comparação por meio do teste de Wilcoxon mostrou que o preparo biomecânico foi eficaz na eliminação dos microrganismos dos canais radiculares em 20% dos casos e o curativo de demora em 62,5%, enquanto que a ação cumulativa do preparo biomecânico e do curativo de demora eliminou os microrganismos em 70,0% dos casos (p<0.001). Pôde-se concluir que o preparo biomecânico, isoladamente, apresentou resultados microbiológicos inferiores àqueles obtidos quando o mesmo foi associado ao curativo de demora, mostrando a necessidade de aplicação tópica de um curativo de demora entre sessões em dentes decíduos portadores de necrose pulpar e lesão periapical.